Methods for cell isolation and analysis of the highly regenerative tunicate Polycarpa mytiligera - Gordon, Tal; Hendin, Noam; Wurtzel, Omri (Frontiers in Cell and Developmental Biology, 2023)
Background: Polycarpa mytiligera is the only molecularly characterized solitary ascidian capable of regenerating all organs and tissue types. The cellular basis for regeneration in P. mytiligera is largely unknown, and methods for isolating live cells from this species for functional analyses are unavailable. Results: Here, we developed a method for isolating live cells from P. mytiligera, overcoming major experimental challenges, including the dissociation of its thick body wall and native cellular autofluorescence. We demonstrated the applicability of our approach for tissue dissociation and cell analysis using three flow cytometry platforms, and by using broadly used non-species-specific cell labeling reagents. In addition to live cell isolation, proof-of-concept experiments showed that this approach was compatible with gene expression analysis of RNA extracted from the isolated cells, and with ex vivo analysis of phagocytosis. We presented efficient methods for cell purification from a highly regenerative ascidian, which could be transferable to diversity of non-model marine organisms. The ability to purify live cells will promote future studies of cell function in P. mytiligera regeneration.